2022
DOI: 10.3390/met12061055
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Optical Imaging of Arbitrarily Distributed Defects in Welds under Combined Magnetic Field

Abstract: Using the traditional magneto-optical detection methods, micro-weld defects parallel with the magnetic field direction may be overlooked. In order to overcome this, a non-destructive testing method based on magneto-optical imaging under a vertical combined magnetic field (VCMF) is proposed. To demonstrate this, the experimental results of the magneto-optical imaging of weld defects excited by a vertical combined magnetic field (VCMF) or parallel combined magnetic field (PCMF) are compared with those of traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This procedure is a non-destructive testing based on magneto-optical (MO) imaging, which transforms the magnetic leakage field into a light intensity map to visualize defects [77][78][79]. In the study [80], a vertical combined magnetic field (VCNF) and a parallel combined magnetic field (PCMF) were compared to traditional magnetic fields where it was found that magneto-optical imaging under VCMF could detect weld defects of any shape and distribution accurately. This technique was also used in [81], where weld surface and subsurface cracks were detected by an MO sensor.…”
Section: Magneto-optical Detection Methodsmentioning
confidence: 99%
“…This procedure is a non-destructive testing based on magneto-optical (MO) imaging, which transforms the magnetic leakage field into a light intensity map to visualize defects [77][78][79]. In the study [80], a vertical combined magnetic field (VCNF) and a parallel combined magnetic field (PCMF) were compared to traditional magnetic fields where it was found that magneto-optical imaging under VCMF could detect weld defects of any shape and distribution accurately. This technique was also used in [81], where weld surface and subsurface cracks were detected by an MO sensor.…”
Section: Magneto-optical Detection Methodsmentioning
confidence: 99%
“…AC induced magnetic field has a scale effect that produces a concentrated field on the surface [16]. Magnetooptical imaging under a vertical combined magnetic field [17] As per inspection standards, ASME Section-V, Article-7 (magnetic particle examination) and SE709 (standard practice for magnetic particle examination) and ASME Section-VIII, Division 1, the procedure followed for MPT is as follows:…”
Section: Magnetic Particle Testingmentioning
confidence: 99%